Criminological perspective in corruption crimes committed by TNI army soldiers (Case Study of Decision Number: 21-K/PMT-II/AD/II/2022 and Case Study of Decision Number: 44-K/Connection/PMT-II/AD/VIII/2022) - Saddam Febrianto (Dynamics of Politics and Democracy, 2023)
Purpose: This study aims to analyze the Criminological Perspective in Corruption Crimes Committed by TNI AD Soldiers (Case Study of Decision Number: 21-K/PMT-II/AD/II/2022 and Case Study of Decision Number: 44-K/Koneksitas/PMT-II/AD/VIII/2022). Research/methodology: The type of research in this study uses the normative juridical research type. This type of normative juridical research is research that uses or refers to legal norms that can be in laws and regulations that refer to legal norms. The author conducted research, which is descriptive and analytical. Data analysis was carried out using qualitative analysis methods. Results: The result of a construction analysis that underpins the TNI AD soldiers to commit corruption crimes in juridical studies and criminological studies is the nature of the juridical study that the author analyzes from the two corruption convictions that have been tried in this connection court is that the defendant is legally and justifiably proven to have committed a corruption crime and has been sentenced to a heavy prison sentence accompanied by a large fine and the existence of a criminal additional in the form of replacement money. Analysis Results Regarding the case raised in this study regarding the connection of corruption crimes committed by the military and civilians, the panel of judges has imposed heavy criminal sanctions on the perpetrators, this is actually from two things, namely justice for the victim and justice for the perpetrator. The perpetrator for his actions has been sentenced with heavy sanctions.